2022
DOI: 10.1177/10775463221077490
|View full text |Cite
|
Sign up to set email alerts
|

Proper location of the transducers for an active noise barrier

Abstract: The main intention of this study is to propose general criteria for the locations of the control sources and error microphones that improve the performance of the active noise barrier. Based on the proposed criteria of this study, the greater reduction is attained when the diffracted field of the noise source is canceled with the diffracted field of the control sources, that is, it is suggested to locate the control sources on the incident side and below the path that connects the furthest point in the shadow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…where Z P is the vector of complex acoustic transfer impedances of the primary source with a strength of q P , and Z s is an M × N matrix, corresponds to the transfer impedance matrix of N control sources at the positions of M points. In equation (6), q s denotes the vector of the complex strength of the control source, 26 and is determined by minimizing the total squared pressure at the error microphones. The total squared acoustic pressure is expressed in equation ( 7)…”
Section: Diffraction Modelmentioning
confidence: 99%
See 3 more Smart Citations
“…where Z P is the vector of complex acoustic transfer impedances of the primary source with a strength of q P , and Z s is an M × N matrix, corresponds to the transfer impedance matrix of N control sources at the positions of M points. In equation (6), q s denotes the vector of the complex strength of the control source, 26 and is determined by minimizing the total squared pressure at the error microphones. The total squared acoustic pressure is expressed in equation ( 7)…”
Section: Diffraction Modelmentioning
confidence: 99%
“…Research has shown that active noise control significantly enhances the performance of acoustic barriers at low-frequency noise bands. [1][2][3][4] Despite the existence of various parameters that affect the efficiency of active noise barriers, few studies have optimized them. [5][6][7] Some of these parameters include the number, location, and distance between adjacent control sources and error microphones.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By placing speakers and error microphones above the barrier, the diffracted noise in a low-frequency band is reduced through ANC. The arrangement of microphones and speakers 8 , 9 , the method of obtaining the control filter 10 , 11 , and using unidirectional control sources 12 have been studied to improve the performance of the active noise barrier. However, the active noise barrier using semi-infinite barrier is expensive and requires a large place to set up.…”
Section: Introductionmentioning
confidence: 99%